Application of the Problem Solving Learning Model in Improving Science Learning Outcomes of Class VI Students of UPT SD Negeri 6 Pangkajene Sidenreng Rappang District - Amelia Putri; Usman M; Syamsunir Syamsunir; Hasanuddin Hasanuddin; Hasan Hasan (Edumaspul: Jurnal Pendidikan, 2024)
Low learning outcomes are a problem in this research. The question asked was whether class VI students at UPT SD Negeri 6 Pangkajene, Sidenreng Rappang Regency would learn better by using the Problem Solving learning approach. This research was carried out to find out whether the results of students' science subjects had improved. The type of research used is CAR, the methodology used is qualitative. Procedures and outcomes are the primary focus of the investigation. The research was conducted at UPT SD Negeri 6 Pangkajene, Sidenreng Rappang Regency. Teachers and students of class VI UPT SD Negeri 6 Pangkajene were used as research subjects. There are 18 students registered for the 2023–2024 academic year, divided into 10 female students and 8 male students, carried out in two cycles. Each cycle has 4 stages, namely planning, implementation, observation and reflection. Based on the information generated in cycles I and II, implementation data was collected through the observation, test results, learning and documentation stages. The results of cycle I research are included in category (C) for process emphasis and category (C) for results focus. Meanwhile, in cycle II it can be categorized as (B). The results of the research that has been carried out have increased learning outcomes in science content regarding sources of electrical energy and distribution of electrical energy.